Evaluation of Inclusive Education Program in Class 1 SDN Cinunuk 02 Using CIPP Model (Context, Input, Process, Product) - Lailatul Qurrota Ayuni; Restu Rahayu; Neng Nisa Audina Agustina; Dewi Sunengsih; Rida Nazmi Farhani; Ikrima Bara Sofia; Anisa Julia Dwi Putri; Rifa Fauziah Kamal; Triana Lestari (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
Inclusive education in elementary schools aims to provide equal opportunities for ABK to develop their potential. This research aims to evaluate the implementation of inclusive education at SDN Cinunuk 02 using the CIPP (Context, Input, Process, Product) model. This research methodology involves observation, interviews, and documentation of school principals, class teachers, special support teachers, and ABK. Data analysis was carried out descriptively qualitatively using the CIPP approach to identify challenges and recommendations in increasing the effectiveness of inclusive education. It is hoped that the research results will provide an overview of the implementation and improvement of inclusive education programs in elementary schools. Evaluation of the inclusive education program at SDN Cinunuk 02 using the CIPP (Context, Input, Process, Product) model shows significant results but also faces several challenges. In the context aspect, although the facilities and infrastructure are supportive, the lack of special training for teachers is the main obstacle. In terms of input, the acceptance of students with special needs with certain requirements and a curriculum that is not yet fully inclusive shows the need for improvement. The learning process using interactive lecture methods and individual guidance for students with special needs is effective, but needs to be improved in monitoring and adjusting the material. Evaluation results show positive developments in students with special needs, although there are variations in their achievements. The implication of these findings is the need for regular training for teachers, curriculum adjustments, and increased interaction between normal students and special needs students to improve the effectiveness of inclusive education at SDN Cinunuk 02.